HEMODYNAMIC DISTURBANCES - PATHOGENETIC BASIS TISSUE PATHOLOGY OF THE MAXILLOFACIAL AREA AND BRAIN DAMAGE IN CATAMNESIS SYNDROME PATIENTS INTRAUTERINE GROWTH - Garmash, O.V.; Nazaryan, R.S.; Nazarenko, L.G.; Likhachevа, N.V.; Babajanyan, E.N. (World of Medicine and Biology, 2013)
The aim of our study was to reveal the connection between cerebral haemodynamic disorders of children with IUGR and their dental status. 24 childent with IUGR were examinated. Clinical and static examination methods were used. Mentioned examination methods have shown high prevalence of maxillofacial diseases of children with IUGR syndrome. It was concluded, that the most powerfull disorders of dentition system under the IUGR syndrome are typical for symmetric type of the disease, where the most expressed changes of cerebral haemodynamic were diagnosed.
Keywords: intrauterine growth retardation syndrome; oral cavity; cerebral hemodynamics